To evaluate the support required by staff in the Paediatric Unit in Dora Nginza Hospital in Port Elizabeth, South Africa in caring for children with life limiting and life threatening illnesses - Ureche, Florentina (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references.